Digital Marketing Adoption Among Food Products Home Industry: A Study of Melinjo Chips Producer In Bantul - Akhmadi, Heri (Berkala Ilmiah AGRIDEVINA, 2021)
Digital marketing has become a new trend recently, which is not only applied by large-scale industries but also small industries. Similarly, melinjo chips home industries producer, some of whom have implemented digital marketing using their devices. This study aims to describe the marketing conditions of the melinjo chips and to determine the perceptions of melinjo chips producers towards the adoption of digital marketing. Data were collected through interviews with 63 producers of the melinjo chips selected using census method from all producers in Pandak District, Bantul Regency, Yogyakarta Special Region. Descriptive analysis and 5-point Likert Scale were used to determine the producers’ perception of the adoption of digital marketing in the marketing of melinjo chips. The results showed that in general, the marketing of melinjo chips was mostly using conventional marketing, although some producers have implemented digital marketing. Moreover, the adoption of digital marketing was perceived in neutral category. The neutral perception was due to the fact that although the adoption of digital marketing has positive view such as benefits, and marketing efficiency, there were also obstacles in using it, not providing innovation and low trust in digital marketing technology. DOI : https://doi.org/10.33005/adv.v10i1.2614